Association of Milk and Dairy Products Consumption During Pregnancy with Fetal and Neonatal Head Circumferences: A Systematic Review - Razieh Karimbeiki; Seyedeh Masomeh Derakhshandeh Rishehri; Roya Kelishadi; Motahar Heidari-Beni (Mazandaran University of Medical Sciences, 2017)
Context: Milk and dairy products consumed by mothers seem to be effective for fetal and neonatal anthropometric measurements, because they contain various nutrients. Objectives: The aim of this study was to systematically review the influence of milk and dairy products consumption by mothers on fetal and neonatal head circumferences. Data Sources: Systematic searches were conducted in electronic databases including PubMed/MEDLINE, Scopus, ISI, Ovid, Embase, Medlib, Google Scholar, clinical trials and Cochrane central register of clinical trials. Study Selection: All studies that assessed the relationship between milk and dairy products consumption in healthy females during pregnancy and fetal and neonatal head circumferences were included in our systematic review. Finally, seven studies were relevant that included five cohort studies, one cross-sectional study and one randomized clinical trial. Data Extraction: This systematic review was performed based on the preferred reporting item for systematic reviews and meta-analysis (PRISMA) statement recommendation, and for quality assessment, the Newcastle-Ottawa scale (NOS) for cohort studies, the adapted NOS for a cross-sectional study and the Jadad quality assessment score for a randomized clinical trial, were used. Results: Seven studies that comprised of more than 50000 pregnant females were included in this review. One cohort study, one cross-sectional study and one randomized controlled trial study showed that milk or dairy products consumption by pregnant mothers was not associated with neonatal birth head circumference, while three cohort studies reported that maternal milk or dairy products intake had a positive effect on neonatal birth head circumference. Two cohort studies showed that there was no relationship between maternal milk or dairy products consumption and fetal head circumference while a cross-sectional study reported that there was a positive relationship between milk or dairy products consumption during pregnancy and fetal head circumference. Conclusions: Evidences in this field are limited and inconsistent. According to the findings, there is a positive association between milk and dairy products consumption by pregnant mothers and neonatal birth head circumference but there is no relationship between maternal milk and dairy products consumption and fetal head circumference. However, almost all studies emphasized the importance of milk and dairy products in the maternal diet as a source of valuable nutrients.